Learning environments matter: Identifying influences on the motivation to learn science - Salomé Schulze; Mark van Heerden (South African Journal of Education, 2015)
In the light of the poor academic achievement in science by secondary school students in South Africa, students' motivation for science learning should be enhanced. It is argued that this can only be achieved with insight into which motivational factors to target, with due consideration of the diversity in schools. The study therefore explored the impact of six motivational factors for science learning in a sample of 380 Grade Nine boys and girls from three racial groups, in both public and independent schools. The students completed the Student Motivation for Science Learning questionnaire. Significant differences were identified between different groups and school types. The study is important for identifying the key role of achievement goals, science learning values and science self-efficacies. The main finding emphasises the significant role played by science teachers in motivating students for science in terms of the learning environments that they create. This has important implications for future research, aimed at a better understanding of these environments. Such insights are needed to promote scientific literacy among the school students, and so contribute to the improvement of science achievement in South Africa.